2019
DOI: 10.1101/818559
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

How do species barriers decay? Concordance and local introgression in mosaic hybrid zones of mussels

Abstract: When the ranges of closely-related lineages are large, and overlapping, we can often study introgression at many "replicated" contacts, with different locations and spatial scales. Here we analysed multiple contact zones of the M. edulis complex of marine mussel species, which represent a mosaic distribution of heterogeneously differentiated, semi-isolated genomes. Our aim was to contrast ongoing introgression at the heart of hybrid zones, with past introgression between similar parental populations, at increa… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 89 publications
0
13
0
Order By: Relevance
“…Naturally admixed Atl. M. galloprovincialis combine an old history of introgression during glacial oscillation periods (Fraïsse, Roux, et al, 2018;Roux et al, 2014) with ongoing local introgression from the native M. edulis populations in direct contact within the mosaic hybrid zone observed today Simon et al, 2019). Shared colonisation history cannot be the whole story, however, because we also found repeatable patterns between admixture events that must be considered independent.…”
Section: Parallelism Of Distortionsmentioning
confidence: 74%
See 4 more Smart Citations
“…Naturally admixed Atl. M. galloprovincialis combine an old history of introgression during glacial oscillation periods (Fraïsse, Roux, et al, 2018;Roux et al, 2014) with ongoing local introgression from the native M. edulis populations in direct contact within the mosaic hybrid zone observed today Simon et al, 2019). Shared colonisation history cannot be the whole story, however, because we also found repeatable patterns between admixture events that must be considered independent.…”
Section: Parallelism Of Distortionsmentioning
confidence: 74%
“…Another study showed that the introduction on the Pacific coast of the USA was similarly composed by pure Med. M. galloprovincialis (Simon et al, 2019). Those observations preclude the idea that previously observed Med.…”
Section: Additional Putative Anthropogenic Introductionsmentioning
confidence: 72%
See 3 more Smart Citations